PENGARUH PEMBELAJARAN BERBASIS BUDAYA LOKAL DAN NILAI KEBHINNEKAAN TERHADAP HASIL BELAJAR SISWA PELAJARAN IPS DI SD NEGERI 067774 KECAMATAN MEDAN JOHOR - Tina Sheba Cornelia; Juwita Tindaon (Universitas Quality, 2019)
This study aims to find out: 1) The difference between students 'social studies learning outcomes taught by local cultural-based learning approaches and students' social learning outcomes taught by conventional approaches; 2) Differences in social studies learning outcomes of students who have high diversity values compared to social studies learning outcomes of students who have low diversity values; and 3) Interaction between learning approaches and diversity values towards students' social studies learning outcomes. This research was conducted at 067774 Public Elementary School, Medan Johor District. The population in this study was fifth grade students consisting of 50 students. Data collection techniques in this study were the diversity of questionnaires and social studies learning achievement tests. The method used is quasi experiment with 2x2 factorial design. Data analysis techniques using two-way ANAVA at a significant level α = 0.05. The results showed that: (1) There was a difference between the learning outcomes of students who were taught with the approach to learning based on local culture and the learning outcomes of students who were taught with conventional approaches (Fcount = 17.064; sig. = 0,000 <0.05); (2) There are differences in social studies learning outcomes of students who have high diversity values compared with social studies learning outcomes of students who have low diversity values (Fcount = 10.602; sig. = 0.002 <0.05); and (3) There is an interaction between learning approaches and diversity values in influencing social studies learning outcomes (Fcount = 22.115; sig. = 0.000 <0.05). The results of this study indicate that the learning approach and diversity values influence the students' social studies learning outcomes.